(untitled) (International Journal of Engineering and Computer Science, 2015)
Recently, in the world of digital technologies especially in computer world, there is a tremendous increase in crimes. So investigation of such cases deserves a much more importance. Computer Investigation is the process of uncovering and interpreting process of electronic data for use in computer forensic analysis. Text clustering is an automatic grouping of text documents into clusters so that documents within a cluster have high similarity in comparison to one another, but are dissimilar to documents in other clusters. We are carrying out extensive experimentation with two well-known clustering algorithms K-means and Hierarchical single/Complete/Average Link. In this the number of unstructured text files is given as input and the output is generated in structured format. Previous experiments have been performed with different combinations of algorithms and parameters. Related studies in the literature are significantly more limited than our study. Our studies show that the K-means and Hierarchical algorithms provide the best results for our application domain.